Colocalized targeting of TGF-β and PD-L1 by bintrafusp alfa elicits distinct antitumor responses. Issue 7 (20th July 2022) - Lan, Yan; Yeung, Tsz-Lun; Huang, Hui; Wegener, Ansgar A; Saha, Somdutta; Toister-Achituv, Mira; Jenkins, Molly H; Chiu, Li-Ya; Lazorchak, Adam; Tarcic, Ohad; Wang, Hong; Qi, Jin; et al.
Abstract : Background: Bintrafusp alfa (BA) is a bifunctional fusion protein designed for colocalized, simultaneous inhibition of two immunosuppressive pathways, transforming growth factor-β (TGF-β) and programmed death-ligand 1 (PD-L1), within the tumor microenvironment (TME). We hypothesized that targeting PD-L1 to the tumor by BA colocalizes the TGF-β trap (TGF-βRII) to the TME, enabling it to sequester TGF-β in the tumor more effectively than systemic TGF-β blockade, thereby enhancing antitumor activity. Methods: Multiple technologies were used to characterize the TGF-β trap binding avidity. BA versus combinations of anti-PD-L1 and TGF-β trap or the pan-TGF-β antibody fresolimumab were compared in proliferation and two-way mixed lymphocyte reaction assays. Immunophenotyping of tumor-infiltrating lymphocytes (TILs) and RNA sequencing (RNAseq) analysis assessing stromal and immune landscape following BA or the combination therapy were performed in MC38 tumors. TGF-β and PD-L1 co-expression and their associated gene signatures in MC38 tumors and human lung carcinoma tissue were studied with single-cell RNAseq (scRNAseq) and immunostaining. BA-induced internalization, degradation, and depletion of TGF-β were investigated in vitro. Results: BA and fresolimumab had comparable intrinsic binding to TGF-β1, but there was an ~80× avidity-based increase in binding affinity with BA. BA inhibited cell proliferation in TGF-β-dependent and PD-L1-expressing cells more potently than TGF-β trap or fresolimumab. Compared with the combination of anti-PD-L1 and TGF-β trap or fresolimumab, BA enhanced T cell activation in vitro and increased TILs in MC38 tumors, which correlated with efficacy. BA induced distinct gene expression in the TME compared with the combination therapy, including upregulation of immune-related gene signatures and reduced activities in TGF-β-regulated pathways, such as epithelial-mesenchymal transition, extracellular matrix deposition, and fibrosis. Regulatory T cells, macrophages, immune cells of myeloid lineage, and fibroblasts were key PD-L1/TGF-β1 co-expressing cells in the TME. scRNAseq analysis suggested BA modulation of the macrophage phenotype, which was confirmed by histological assessment. PD-L1/TGF-β1 co-expression was also seen in human tumors. Finally, BA induced TGF-β1 internalization and degradation in the lysosomes. Conclusion: BA more effectively blocks TGF-β by targeting TGF-β trap to the tumor via PD-L1 binding. Such colocalized targeting elicits distinct and superior antitumor responses relative to single agent combination therapy.